(untitled) (Research, Society and Development, 2023)
The Psidium guajava is a species utilized traditionally to treat many pathologies for presenting a variety of phytochemicals, for: flavonoids, terpenoids, tannins, cineol, β-karyophylene. With the intent of exploring the pharmacological potential of P.guajava, its use for the creation of pharmaceutical products, an integrative review of the literature was made, using the guiding question: "How can the guava tree’s therapeutic potential contribute to the development of new pharmaceutical products?". The searches ocurred in official documents and cientific articles indexed to the ANVISA data base of Scielo, PubMed and Lilacs, during the months of august and september of 2022. The describers used were: Phytotherapy, complementary therapies, Psidium, Therapeutic Action and Pharmaceutical Products being crossed with the help of operator And. Were considered as criteria of inclusion official documents and complete articles available for access, indexed to the aforementioned platforms, in english and portuguese, between 2012 and 2022, and as criteria of exclusion, duplicated studies, studies with thematic escape and that weren’t available for access both free and in full, resulting in an atmosphere of 16 files. The researches has shown that the guava tree presents several therapeutic actions, such as: antioxidant, anti-inflammatory, photoprotective, antibacterial, anticariogenic, anti-tumor, antispasmodic, hypoglycemic, nephroprotective, anti-diarrheal, antinociceptive, healing, cytotoxic, and acts against dermatitis. Therefore, the bioactive compounds of this vegetable can be used for the development of pharmaceutical products with the purpose of expanding the therapeutic options in the market and optimize the patients’ quality of life becoming fundamental to foster cientific researches that discuss about the safety, efficiency and toxicity of the using these metabolites.